Evaluation of membrane fouling by different sludge fractions from a long sludge retention time membrane bio-reactor - Low, Yan Ping. (2009)
Membrane treatment is one of the most rapidly advancing water treatment technologies. The membrane processes are applauded for their ability to produce high quality, consistent product water and most significantly the small space requirement is advantageous when compared to the conventional activated sludge system. However, the high costs resulted from membrane fouling hinder the use of membrane separation processes. Membrane fouling results in a decrease in permeate flux and an increase in operational costs. The high costs involved in membrane fouling avoid many from using the technology despite its many advantages. Fouling is a predominant problem of the membrane technology, thus in this study investigations were aimed towards achieving better understanding of the fouling phenomenon. It was hoped that by doing so, methods could be developed to reduce membrane fouling. In efforts to make precise deductions of the fouling resistances contributed by the activated sludge in a MBR system, the activated sludge obtained from a long sludge retention time MBR (SRT=300 days) was separated into supernatant and solutes. Cross-flow microfiltration tests (0.2 μm pore size) were preformed on these samples to determine the respective resistance contributions of the three sludge components: suspended solids, colloids and solutes. This allows insightful investigations of the resistances put forward by each of these sludge components towards membrane fouling. As membrane hydraulic resistances are generally attributed to four basic fouling mechanisms: internal pore blocking, adsorption of particles onto the outer membrane surface, concentration polarization and also membrane resistance (M. Ousman, 1995), the second part of study involves a series of experimental techniques performed on the fouled membranes obtained at the end of the sludge fractions filtrations, to deduce the relative resistances of each of the four fouling mechanisms existing on the fouled membrane. Observing the “resistances in series” model, we are able to determine the major resistance fouling mechanism. The above experiments were carried out at TMPs 0.05, 0.1, 0.15 and 0.2 MPa. This is to investigate the effects of TMP on membrane fouling. In this study, it was found that the resistances of sludge fractions increase with TMP, with the resistances contributed by the suspended solids being the greatest, followed by colloids then solutes. The results could be accounted to the size of the sludge components. At high TMP, a higher driving force is induced. This resulted in a higher initial flux, which introduced a higher solute flux towards the membrane, thus initiating the formation of cake layer, causing faster flux decline.